Identifying best practices for "Safe Harbor" legislation to protect child sex trafficking victims: Decriminalization alone is not sufficient. (January 2016) - Barnert, Elizabeth S.; Abrams, Susan; Azzi, Veronica F.; Ryan, Gery; Brook, Robert; Chung, Paul J.
Abstract: Several states have recently enacted "Safe Harbor" laws to redirect child victims of commercial sexual exploitation and child sex trafficking from the criminal justice system and into the child welfare system. No comprehensive studies of Safe Harbor law implementation exist. The nine state Safe Harbor laws enacted by 2012 were analyzed to guide state legislators, health professionals, law enforcement agents, child welfare providers, and other responders to the commercial sexual exploitation of children on the development and implementation of state Safe Harbor laws. The authors conducted 32 semi-structured interviews with Safe Harbor experts in these states. Participants conveyed that Safe Harbor legislation signified a critical paradigm shift, treating commercially sexually exploited youth not as criminals but as vulnerable children in need of services. However, Safe Harbor legislation varied widely and significant gaps in laws exist. Such laws alone were considered insufficient without adequate funding for necessary services. As a result, many well-meaning providers were going around the Safe Harbor laws by continuing to incarcerate commercially sexually exploited youth in the juvenile justice system regardless of Safe Harbor laws in place. This was done, to act, in their view, in what was the best interest of the victimized children. With imperfect laws and implementation, these findings suggest an important role for local and state responders to act together to protect victims from unnecessary criminalization and potential further traumatization.